Guidance for spiritual mentors. Polemical letters of A. F. Losev in context of discussion about the attitude to july Declaration of metropolitan Sergius (Stragorodsky) - Olga Kosik (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The documents published here were created in the period and in the context of church controversy that took place after the release of the July Declaration of Metropolitan Sergius (Stragorodsky). They date back from the beginning of 1928. The author of the publication puts forward the hypothesis that the two letters belong to the famous philosopher and church fi gure A. F. Losev but were written under the infl uence of the leader of the church opposition Mikhail Alexandrovich Novoselov. Both philosophers were arrested following the case of the “True Orthodox Church”, M. N. Novoselov in 1929, A. F. Losev in 1930. The publication contains two letters to the clergy by A. F. Losev. One of them, the “Letter to the Defender of the Russian Church”, as suggested by the publisher, is addressed to the Athonite elder-Imiaslavets (Russ. имяславец, literally ‘name-praiser’) archimandrite David (Mukhranov). The other, entitled “NN’s Letter to the Elder”, is addressed to the monk of closed-down Zosima’s Hermitage (Зосимова пустынь) Dosifei (Shonin). The letters give reasons for the open severance from Metropolitan Sergius and condemns the compromising or cautious approach to the problem of severance. Looking like a personal document, the letters are designed for a broad audience and bear the function of convincing and attracting adherents of a certain opinion. The letters illustrate a complicated approach to the problem of obeying spiritual authorities, i.e. spiritual fathers and church authorities. Besides, the documents are interesting as a source of information on the church situation in the late 1920s and as a refl ection of complicated spiritual and personal relations arising in this situation. The letters have been discovered in the State Archive of the Russian Federation and in the Central Archive of the Federal Security Service.